PENERAPAN AUDIT DALAM MENILAI KEWAJARAN PENYAJIAN LAPORAN KEUANGAN PADA KOPERASI “X” DI JEMBER - M.Yoga Dharma Putra; Eko Pudjo Laksono; Rizky Eriandani (Jurnal Akuntansi Bisnis, 2017)
This study aims to determine the fairness of presentation of financial statements, visible in the Cooperative "X" in Jember after an external audit conducted primarily in parts prone to misstatements and fraud in the financial statements that management can take immediate preventive measures that misstatements and fraud does not happen again in the cooperatives. Research object is lifted financial statements. The research focuses on the fairness of presentation of financial statements Cooperative "X" engaged in agri commodities TBN tobacco. In the collection and processing of data, the steps taken is to conduct a survey to cooperatives X in Jember to obtain information - information about the overview and organizational conditions. After data collection was conducted through questionnaires, interviews and observation and document analysis Of the results the application of audit for assess the fairness of financial statements business entity the year 2012 known that difference that arises on account sales due business entity wrong recorded sales who not supposed recognized in the year 2012 so that the thing has impact against another account and audit opinion about fairness of financial statements. Cooperative X needs to be more consistent in presenting any corresponding accounts in the financial statements the accounting policies used.Keyword : financial statements, the audit of financial statements, the fair presentation of the financial statements